Answer:
1
Step-by-step explanation:
0=1-x
-1= -x
divide both sides by -1
x=1
Answer:
10(x-3)
Step-by-step explanation:
Answer:
(2, 1 )
Step-by-step explanation:
Given the 2 equations
y = 6x - 11 → (1)
- 2x - 3y = - 7 → (2)
Substitute y = 6x - 11 into (2)
- 2x - 3(6x - 11) = - 7 ← distribute and simplify left side
- 2x - 18x + 33 = - 7
- 20x + 33 = - 7 ( subtract 33 from both sides )
- 20x = - 40 ( divide both sides by - 20 )
x = 2
Substitute x = 2 into (1) for corresponding value of y
y = 6(2) - 11 = 12 - 11 = 1
Solution is (2, 1 )
4×77. 75=311
4×31. 75=127
4×19. 25=77
4×82=328
The first digit can be any one of the numbers 2-9 That a total of 8 numbers.
The next 6 digits can be any permutation of 6 from the numbers 0 to 9.
(10 numbers)
nPr = n! / r!
so here we have 10P6 = 10! / 6! = 10*9*8*7 = 5040
So final answer is 8 * 5040 = 40,320